EFFECTIVE WAYS LEARNING NEW VOCABULARY - Alibekova Z.A, Alibekova Z.A (Журнал иностранных языков и лингвистики, 2021)
The acticle is dedicated to teaching new vocabulary through different methods and aid learners in understanding a new language and new words.